A study on prevalence of anaemia and various factors influencing anaemia among adolescent girls in urban and rural field practice areas of Osmania Medical College - Rani, Gurram Sudha; Baburao, Bollampalli (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescents in India represent over 1/5th (22.3%) of total population. Iron deficiency anaemia is the commonest medical disorder and is a problem of serious public health condition with epidemic proportions. It has significant impact on physical, psychological development, immunity, behaviour, and work performance. The objectives of the study were to determine prevalence of anaemia among adolescent girls and to study the various factors associated with anaemia in urban and rural field practice areas of Osmania Medical College Methods: A total of 760 adolescent girls (380 in each area) were interviewed and examined. BMI was calculated with anthropometric calculator available in WHO anthroplus. Method of haemoglobin estimation is by cyneamethe-heamoglobin. Anaemia was classified based on WHO classification. Results: The prevalence of anaemia was 74.5% and 82.6% in rural and urban area respectively. In rural area, 84 (87.5%) of girls were anaemic who were menstruating more than 7 days and only 31 (45.6%) were anaemic who were menstruating less than 3 days. Majority of married subjects were anaemic in both urban (82.4%) and rural (95.8%) area. Religion did not have significant relation with anaemia. Prevalence of anaemia was more in lower and lower middle class. In the present study majority of thin girls were anaemic in both rural (97.4%) and urban (94.8%) area with significant statistical association. In present study those who were taking meat more than once a week had less percentage of anaemia 38 (36.9). Those respondents who never took green leafy vegetables have more prevalence of anaemia in both areas. All were statistically associated. Conclusions: Anaemia which is a very serious problem in adolescent girls requires urgent action and practicable interventions